Promoting More Physical Activity and Less Sedentary Behaviour During the COVID-19 Situation – SportStudisMoveYou (SSMY): A Randomized Controlled Trial. Issue 1 (8th January 2021) - Nigg, Claudio R.; Aneas Zurkinden, Nando L.; Beck, Damian A.; Bisang, Xaviér J. B.; Charbonnet, Bryan; Dütschler, Benjamin; Felder, Timo M. O.; Ganic, Tarik; Grunder, Lara P.; Gürber, Marc P.; Konyo, Jacqueline; Lehmann, Remo D.; et al.
Objective: To determine the effect of an innovative, online-based intervention, addressing the possible decline of physical activity (PA) and increase of sedentary behavior (SB) during COVID-19 stay at home restrictions in Switzerland. Methods: This study investigated the effect of a two-week, social cognitive theory-based, online-video moderate to vigorous (MV)PA or SB intervention on MVPA and SB behaviour and intention via a 3 group by 2 time point parallel randomized controlled trial during the COVID-19 pandemic. Adults (≥18 yo) were recruited over the internet between April 10th and April 19th 2020 (n = 129; 75.2% female; mean age = 29.0 [SD 11.8] years). Both intervention groups received five videos targeting either SB for the SB group or MVPA for the MVPA group and were compared to an attention control group (fruit and vegetable consumption). It was hypothesized that MVPA time and intention would increase for the MVPA group and the SB group would outperform control on SB behaviour and intention indicators. Results: No significant interactions were found for the MVPA group (n = 41) versus control (n = 40). Only one significant interaction was measured for the SB group (n = 48; intention of active breaks F = (2, 114) = 5.84, p = 0.004, ηp 2 = 0.09). Although mostly non-significant and small effects, the MVPA group showed results pointing in the hypothesized direction on all PA indicators and the SB on all SB indicators, respectively. Conclusion: Considering this study's limitations (e.g. small intervention dose), video-based online PA and SB interventions seem promising and feasible. This approach is appropriate for COVID-19 and other stay at home situations.